Backward ownership, uniform pricing and entry deterrence - Matthias Hunold (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2017)
Entry deterrence can occur when downstream incumbents hold non-controlling ownership shares of a supplier which is commited to charge uniform prices to all downstream firms. The ownership shares imply a rebate on the input price for the incumbents through the profit participation. Such backward ownership induces the supplier to accommodate entry by charging a low uniform price to all downstream firms in case of entry. However, just the entry-accommodating behavior reduces entry profits and thereby can lead to market foreclosure. Based on this theory, the article reviews a merger case in the financial services industry and draws conclusions for regulation and competition policy.
Keywords: G34; L22; L40; 330; entry deterrence; foreclosure; minority shareholdings; non-controlling partial ownership; uniform pricing; vertical integration